(untitled) (Journal of the College of Basic Education, 2023)
TiO2 titanium oxide thin films were prepared by thermal chemical deposition.on bases of borosilicate glass at a temperature (420 o C). The diffraction pattern results showedX-rays The prepared films have a polycrystalline structure.The study included a spectral recording of the absorbance and transmittance of different fishes ofMembranes at the wavelength range (300-900) nm and calculating the absorption coefficient and gapenergy for all transitions. The results showed the effect of changing the membrane thickness on the transitions.electronic absorption coefficient. Likewise, the possibility of direct and indirect electronic transfersdirectly.